Practical Syntheses of Enantiomerically Enriched γ-Lactones and γ-Hydroxy Ketones by the Alkylation of Pseudoephedrine Amides with Epoxides and Their Derivatives - Myers, Andrew G; McKinstry, Lydia (Journal of organic chemistry, 1996)
Pseudoephedrine amide enolates are shown to undergo efficient alkylation reactions with epoxides as electrophiles. Reactions with monosubstituted epoxides are subject to stereochemical matching such that the pairing leading to the 1,3-syn diastereomer is a highly selective, synthetically useful process, while the pairing forming the 1,3-anti diastereomer is not. Reactions with the 1,1-disubstituted epoxide isobutylene oxide are also highly diastereoselective and synthetically useful, but ethylene oxide exhibits poor diastereoselectivity. As an alternative to the use of ethylene oxide, 2-(tert-butyldimethylsilyloxy)ethyl iodide is shown to undergo highly diastereoselective and efficient alkylation reactions with pseudoephedrine amide enolates. Interestingly, epoxides and alkyl halides are found to attack opposite π-faces of pseudoephedrine amide enolates. The products of each of these alkylation reactions are transformed efficiently into γ-lactones by acidic hydrolysis and into methyl ketones by the addition of methyllithium. The methodology described provides useful procedures for the synthesis of enantiomerically enriched γ-lactones and γ-hydroxy ketones.